2013
DOI: 10.1111/all.12257
|View full text |Cite
|
Sign up to set email alerts
|

Birch pollen sensitization with cross-reactivity to food allergens predominates in adults with eosinophilic esophagitis

Abstract: EoE patients show variable sensitization patterns to food and aeroallergens. The value of allergy testing in adult EoE patients is unclear. Component-resolved diagnosis (CRD) may offer additional insights into sensitization patterns. The aim of this study was to characterize sensitization patterns in adult EoE patients using CRD. Serum from 76 patients (17 female), age 38.6 ± 1.5 years, was analyzed for reactivity to 112 different allergen components using an immuno-solid-phase allergen chip (ISAC). We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 15 publications
(24 reference statements)
2
65
0
1
Order By: Relevance
“…6,24 Whereas food antigens are primarily identified as the allergic triggers, inhaled aeroallergens have also been implicated in some patients; this finding may represent a manifestation of cross-sensitization to food allergens. 25 Indeed, murine models of eosinophilic esophagitis can be induced by sensitizing and challenging mice with aeroallergens and ovalbumin 26,27 or by overexpressing the cytokines seen in human eosinophilic esophagitis in the animals. 28 Several lines of evidence suggest that interleukin-5 and interleukin-13 may play a role in the pathogenesis of eosinophilic esophagitis.…”
Section: Enhanced Th2 Activity and Allergic Susceptibilitymentioning
confidence: 99%
“…6,24 Whereas food antigens are primarily identified as the allergic triggers, inhaled aeroallergens have also been implicated in some patients; this finding may represent a manifestation of cross-sensitization to food allergens. 25 Indeed, murine models of eosinophilic esophagitis can be induced by sensitizing and challenging mice with aeroallergens and ovalbumin 26,27 or by overexpressing the cytokines seen in human eosinophilic esophagitis in the animals. 28 Several lines of evidence suggest that interleukin-5 and interleukin-13 may play a role in the pathogenesis of eosinophilic esophagitis.…”
Section: Enhanced Th2 Activity and Allergic Susceptibilitymentioning
confidence: 99%
“…2 This counters previous assertions that cross -sensitisation to birch pollen explains food antigenicity in EoE. 11 Dedicated studies using endoscopic sampling following high concentration aero-antigen exposure may resolve this issue.…”
mentioning
confidence: 94%
“…Some authors reported that most EoE patients are sensitized to aeroallergens that cross-react with food allergens. In particular, sensitization to profilins and pathogenesis-related protein 10 (PR-10) is very common [11,12], but their significance is very different. In fact, profilins are ubiquitary allergens with an insignificant clinical role, while for PR-10 the relationship with symptoms is acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules, once digested by pepsin, are degraded in the stomach, but are intact when passing through the esophagus, where they can be recognized by the immune system. Van Rhijn et al reported that sensitization to birch pollen (rBet v1) with cross reactivity to foods via PR-10 protein occurs in 39% of adult EoE patients [12]. On the basis of this feature and the fact that PR-10 proteins occur naturally in many common plant foods, they may play an important role in EoE.…”
Section: Introductionmentioning
confidence: 99%